Valorization of waste in sand concrete based on plant fibres - Rihla, Chaher; Hebhoub, Houria; Djebien, Rachid; Abdelouahed, Assia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The introduction of treated plant fibres into sand concretes leads to a reduction in density, improved ductility and thermal conductivity, and makes sand concrete an environmentally friendly and ecological material. The recovery of waste in this type of material allows the production of new ecological and sustainable materials used either in the new construction or in the rehabilitation of old buildings.
Keywords: wastes; sand concrete; wheat straw fibres; ecological material; durability; substitution; odpady; beton piaskowy; słoma; materiał ekologiczny; trwałość